Reflecting a crisis reaction: Narratives from patients with oesophageal cancer about the first 6 months after diagnosis and surgery - Ylva Hellstadius; Marlene Malmström; Pernilla Lagergren; Magnus Sundbom; Anna Wikman (Wiley, 2019)
Abstract Aim The aim of the study was to describe patients' experiences of emotional adaption following treatment for oesophageal cancer from diagnosis to 6 months after surgery. Design A qualitative interview study using an inductive approach was carried out. Methods Participants were recruited from two university hospitals in Sweden. Ten patients who had been operated for oesophageal cancer with curative intent 6 months earlier and consented to participate in the study were included. Patients who had a disease recurrence were not eligible for inclusion. Participants were interviewed with a semi‐structured interview approach. Data were analysed using qualitative content analysis. Results One overarching theme was identified; Experiencing a crisis reaction, which comprised three key categories; (a) From emotionally numb to feeling quite alright; (b) From a focus on cure to reflections about a whole new life; and (c) From a severe treatment to suffering an emaciated, non‐compliant body, derived from 14 distinct sub‐categories. Conclusion This study highlights the process of emotional adaptation following oesophageal cancer surgery that patients describe when reflecting back on the first 6 months postoperatively pointing to a crisis reaction in this early postoperative period.